A high-strength glass precursor microsphere that is not easy to absorb moisture, and its preparation method and application
By using the formulation of silica sol, acetate and nitrate under low energy consumption, the cross-linking of silica sol and dispersing of inorganic salts is promoted, which solves the problems of easy moisture absorption, low strength and high energy consumption of glass precursor particles, and achieves the Preparation of glass precursor microspheres that are not easy to absorb moisture and are highly intensive.
Patent Information
- Application Number
- CN202310474600.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-27
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-04-27
AI Technical Summary
In the prior art, when preparing glass precursor particles under low energy consumption conditions, there are problems such as moisture absorption, low strength and high energy consumption.
Using formulas including silica sol, acetate and nitrate, the crosslinking of silica sol is promoted by controlling the molar ratio of acetate and nitrate, and the inorganic salt is dispersed in the silica sol gel grid to inhibit inorganic Crystallization and moisture absorption of salt.
The prepared glass precursor microspheres are not easy to absorb moisture and have high strength. They can remain unshaved for two months without adding stabilizers or polymer binders. They are suitable for further heating and preparation of high-softened glass microspheres or hollows. Glass microspheres.
Smart Images

Figure CN116444133B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft chemical methods, and in particular to a high-strength glass precursor microsphere that is not easy to absorb moisture, and a preparation method and application thereof. Background Art
[0002] Hollow glass microspheres can be used as coatings or thermal insulation materials and are widely used in aerospace, trains, ships and other fields. At present, there are three main methods for preparing hollow glass microspheres: liquid phase atomization method, solid phase powder method and soft chemical method. These three preparation methods can be simply divided into one-step method (liquid phase atomization method) and two-step method (solid phase powder method and soft chemical method) to prepare hollow glass microspheres; among them, although the one-step method is simple, the strength of the prepared hollow glass microspheres is lower than that of the two-step method; and the first step of the two-step method is to prepare glass precursor particles, and the second step is high-temperature vitrification to prepare hollow glass microspheres. In the two-step method, the solid phase powder method needs to be melted at a temperature above 1000°C, then ground, and then classified to obtain glass precursor particles. This method has higher energy consumption and lower yield than the soft chemical method; and the glass precursor particles obtained by the soft chemical method are not easy to dry below 200°C, the yield is reduced, and the yield is increased when the temperature is increased, but the particles still have no strength and absorb moisture seriously, which is not conducive to the second step of high-temperature vitrification. Therefore, there is an urgent need to make further improvements to the problems existing in the preparation of glass precursor particles by soft chemical methods under low energy consumption conditions. Summary of the invention
[0003] In order to solve the above technical problems, the purpose of the present invention is to provide a high-strength glass precursor microsphere that is not easy to absorb moisture and a preparation method and application thereof, so as to solve the problems that the glass precursor particles prepared by the prior art are easy to absorb moisture, have low strength and high energy consumption in the preparation process.
[0004] The technical solution of the present invention to solve the above technical problems is as follows: provide a high-strength glass precursor microsphere that is not easy to absorb moisture, comprising the following raw materials: comprising the following raw materials: silica sol, salt and boric acid, the salt is acetate and nitrate; wherein the molar ratio of acetate in the acetate and nitrate in the nitrate is 3-5:1, the mass ratio of boric acid to silica sol is 6-8:100, and the mass ratio of salt to boric acid is 44-58:6-8.
[0005] The beneficial effects of the present invention are as follows: the glass precursor microspheres of the present invention are not easy to be crushed or deformed without adding a stabilizer or a polymer binder, are not easy to absorb moisture in the air, can last for up to two months without hardening, and can be further heated to prepare high softening point glass microspheres or hollow glass microspheres.
[0006] On the basis of the above technical solution, the present invention can also be improved as follows:
[0007] Furthermore, the following raw materials are included: silica sol, salt and boric acid, wherein the salt is acetate and nitrate; wherein the molar ratio of acetate in the acetate and nitrate in the nitrate is 3-5:1, the mass ratio of boric acid to silica sol is 7:100, and the mass ratio of salt to boric acid is 51:7.
[0008] Furthermore, SiO in silica sol 2 The mass fraction of SiO is 10-30%, 2 The particle diameter is 1-20nm.
[0009] Furthermore, SiO in silica sol 2 The mass fraction of SiO is 30%, 2 The particle diameter is 10-20nm.
[0010] Furthermore, the acetate is a mixture of two or three of calcium acetate, lithium acetate, aluminum acetate, sodium acetate and potassium acetate.
[0011] Furthermore, the acetate is a mixture of calcium acetate and lithium acetate.
[0012] Furthermore, the nitrate is a mixture of 3-5 of calcium nitrate, lithium nitrate, aluminum nitrate, sodium nitrate, potassium nitrate and magnesium nitrate.
[0013] Further, the nitrate is a mixture of aluminum nitrate, sodium nitrate, potassium nitrate and magnesium nitrate.
[0014] Furthermore, Ca in salt 2+ , Li + 、Al 3+ 、Na + , K + Mg 2+ The molar ratio is 15-18:18-20:1:4-8:1-5:1-5.
[0015] Furthermore, Ca in salt 2+ , Li + 、Al 3+ 、Na + , K + Mg 2+ The molar ratio is 16:19:1:6:3:2.5.
[0016] The present invention also provides a method for preparing the above-mentioned high-strength glass precursor microspheres that are not easy to absorb moisture, comprising the following steps:
[0017] (1) respectively adding water to the raw materials acetate, nitrate and boric acid to prepare a raw material aqueous solution, and then mixing them evenly to obtain a mixed solution;
[0018] (2) heating the mixed solution obtained in step (1) under stirring conditions, diluting the silica sol with water, and then adding the diluted silica sol by atomization to obtain a white emulsion;
[0019] (3) spray drying the white emulsion obtained in step (2) to obtain high-strength glass precursor microspheres that are not easy to absorb moisture.
[0020] Furthermore, in step (1), the mass concentration of the raw aqueous solution is 8-12%.
[0021] Furthermore, in step (1), the pH value of the mixed solution is 5-6.
[0022] Furthermore, in step (2), heating is performed to 40-70°C.
[0023] Furthermore, in step (2), the mass fraction of the silica sol after dilution is 0.5-0.8 times the mass fraction before dilution.
[0024] Furthermore, in step (2), the pH value of the white emulsion is 5.5-7.
[0025] Furthermore, in step (3), spray drying is performed at 120-200°C.
[0026] Furthermore, the spray drying parameters are: air inlet pressure 3.5-6 atmospheres, air inlet volume 300-400m 3 / h, inlet air temperature 120-200℃.
[0027] Furthermore, in step (3), the moisture content of the high-strength glass precursor microspheres that are not easy to absorb moisture is ≤8wt%, and the diameter is 5-40μm.
[0028] The present invention also provides application of the microspheres in the preparation of hollow glass microspheres.
[0029] The present invention has the following beneficial effects:
[0030] 1. The formula of the present invention controls the ratio of two anions (acetate and nitrate) so that the silica sol undergoes further cross-linking at the spray drying temperature, and disperses and adheres various inorganic salts in the grid of the silica sol gel, thereby inhibiting the crystallization and growth of the inorganic salts and reducing the moisture absorption capacity of the inorganic salts. In addition, due to the further cross-linking of the silica sol, the strength of the precursor microspheres is enhanced. Therefore, the glass precursor microspheres prepared by the formula are not only not easy to absorb moisture, but also have high strength.
[0031] 2. The preparation method of the present invention is simple, has low energy consumption and low cost, and the glass precursor microspheres are not easy to absorb moisture, have high strength, and are convenient to store and transport. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1This is the SEM image of the microspheres prepared in Example 1;
[0033] Figure 2 This is a cross-sectional SEM image of the microspheres prepared in Example 1;
[0034] Figure 3 This is the SEM image of the microspheres prepared in Example 4;
[0035] Figure 4 This is the SEM image of the microspheres prepared in Comparative Example 1;
[0036] Figure 5 This is the SEM image of the microspheres prepared in Comparative Example 2. DETAILED DESCRIPTION
[0037] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0038] Embodiment 1:
[0039] A high-strength glass precursor microsphere that is not easy to absorb moisture, comprising the following raw materials: silica sol (SiO 2 The mass fraction of SiO is 30%, 2 10 nm in diameter), acetate (a mixture of calcium acetate and lithium acetate), nitrate (a mixture of aluminum nitrate, sodium nitrate, potassium nitrate and magnesium nitrate) and boric acid;
[0040] The molar ratio of acetate to nitrate is 3:1, the mass ratio of boric acid to silica sol is 7:100, the mass ratio of the total mass of acetate and nitrate to boric acid is 51:7, and the Ca content of the mixture of acetate and nitrate is 2.3477 g / cm2. 2+ , Li + 、Al 3+ 、Na + , K + Mg 2+ The molar ratio is 16:19:1:6:3:2.5.
[0041] A method for preparing high-strength glass precursor microspheres that are not easy to absorb moisture, comprising the following steps:
[0042] (1) respectively adding water to the raw materials acetate, nitrate and boric acid to prepare a raw material aqueous solution (mass concentration of 10%), and then mixing them evenly to obtain a mixed solution (pH = 5.4);
[0043] (2) heating the mixed solution obtained in step (1) to 45° C. under stirring, diluting the silica sol with water (the mass fraction after dilution is 15%), and adding the silica sol by atomization through a spray gun to obtain a white emulsion (pH=5.6);
[0044] (3) The white emulsion obtained in step (2) was spray dried by a spray dryer at 185° C. The spray drying parameters were: inlet air pressure 4 atmospheres, inlet air volume 350 m 3 / h, with an inlet air temperature of 185°C, high-strength glass precursor microspheres with a diameter of 27 μm that are not easy to absorb moisture are produced.
[0045] Embodiment 2:
[0046] A high-strength glass precursor microsphere that is not easy to absorb moisture, comprising the following raw materials: silica sol (SiO 2 The mass fraction of SiO is 10%, 2 1 nm in diameter), acetate (a mixture of calcium acetate and lithium acetate), nitrate (a mixture of aluminum nitrate, sodium nitrate, potassium nitrate and magnesium nitrate) and boric acid;
[0047] The molar ratio of acetate to nitrate is 5:1, the mass ratio of boric acid to silica sol is 6:100, the mass ratio of the total mass of acetate and nitrate to boric acid is 44:6, and the Ca content of the mixture of acetate and nitrate is 2.3477 g / cm2. 2+ , Li + 、Al 3+ 、Na + , K + Mg 2+ The molar ratio is 15:18:1:4:1:1.
[0048] A method for preparing high-strength glass precursor microspheres that are not easy to absorb moisture, comprising the following steps:
[0049] (1) adding water to the raw materials acetate, nitrate and boric acid to prepare a raw material aqueous solution (mass concentration of 8%), and then mixing them evenly to obtain a mixed solution (pH = 5.7);
[0050] (2) heating the mixed solution obtained in step (1) to 40° C. under stirring, diluting the silica sol with water (the mass fraction after dilution is 8%), and adding the silica sol by atomization through a spray gun to obtain a white emulsion (pH=5.9);
[0051] (3) The white emulsion obtained in step (2) was spray dried by a spray dryer at 120° C. The spray drying parameters were: inlet air pressure 6 atmospheres, inlet air volume 300m 3 / h, with an inlet air temperature of 120°C, high-strength glass precursor microspheres with a diameter of 5 μm that are not easy to absorb moisture are obtained.
[0052] Embodiment 3:
[0053] A high-strength glass precursor microsphere that is not easy to absorb moisture, comprising the following raw materials: silica sol (SiO 2 The mass fraction of SiO is 20%, 2 20 nm in diameter), acetate (a mixture of calcium acetate, lithium acetate, and potassium acetate), nitrate (a mixture of aluminum nitrate, sodium nitrate, and magnesium nitrate), and boric acid;
[0054] The molar ratio of acetate to nitrate is 5:1, the mass ratio of boric acid to silica sol is 8:100, the mass ratio of the total mass of acetate and nitrate to boric acid is 58:8, and the Ca content of the mixture of acetate and nitrate is 2.3477 g / cm2. 2+ , Li + 、Al 3+ 、Na + , K + Mg 2+ The molar ratio is 18:20:1:8:5:2.
[0055] A method for preparing high-strength glass precursor microspheres that are not easy to absorb moisture, comprising the following steps:
[0056] (1) adding water to the raw materials acetate, nitrate and boric acid to prepare a raw material aqueous solution (mass concentration of 12%), and then mixing them evenly to obtain a mixed solution (pH = 5.9);
[0057] (2) heating the mixed solution obtained in step (1) to 70° C. under stirring, diluting the silica sol with water (the mass fraction after dilution is 12%), and adding the silica sol by atomization through a spray gun to obtain a white emulsion (pH=6.2);
[0058] (3) The white emulsion obtained in step (2) was spray dried by a spray dryer at 200° C. The spray drying parameters were: inlet air pressure 3.5 atmospheres, inlet air volume 400 m 3 / h, with an inlet air temperature of 200°C, high-strength glass precursor microspheres with a diameter of 40 μm that are not easy to absorb moisture are obtained.
[0059] Embodiment 4:
[0060] A high-strength glass precursor microsphere that is not easy to absorb moisture comprises the following raw materials: the molar ratio of acetate to nitrate is 4:1, and the rest is the same as in Example 1.
[0061] A method for preparing high-strength glass precursor microspheres that are not easy to absorb moisture, comprising the following steps:
[0062] Same as Example 1.
[0063] Comparative Example 1:
[0064] A glass precursor microsphere comprises the following raw materials: the acetate in Example 1 is replaced with the corresponding nitrate, and the rest is the same as Example 1.
[0065] A method for preparing glass precursor microspheres comprises the following steps:
[0066] As in Example 1, the pH of the prepared mixed solution was 2.5, and the pH of the white emulsion was 3.5.
[0067] Comparative Example 2:
[0068] A glass precursor microsphere comprises the following raw materials: the molar ratio of acetate to nitrate is 2.6:1, the acetate is a mixture of calcium acetate, sodium acetate, potassium acetate, magnesium acetate and aluminum acetate, the nitrate is lithium nitrate, and the rest is the same as in Example 1.
[0069] A method for preparing glass precursor microspheres comprises the following steps:
[0070] As in Example 1, the pH of the prepared mixed solution was 6, and the pH of the white emulsion was 6.5.
[0071] Test example
[0072] 1. The microspheres and microsphere cross-sections prepared in Example 1 were subjected to SEM examination, and the results are shown in Figure 1-2 .
[0073] Depend on Figure 1-2 It can be seen that the microspheres are completely gelled, dense inside and outside, and have a hard texture.
[0074] 2. The microspheres prepared in Example 4 and Comparative Examples 1-2 were subjected to SEM examination. The results are shown in Figure 3-5 .
[0075] Depend on Figure 3 It can be seen that the microspheres prepared in Example 4 are not easy to absorb moisture, have little breakage after rolling, and have high strength;
[0076] Depend on Figure 4 It can be seen that the microspheres prepared in Comparative Example 1 absorb moisture seriously. The edge of the sample can be seen in the scanning electron microscope picture to be water-like, and the microspheres have no strength. During the sample preparation process, the sample is gently spread with a spoon. The sample in the picture is muddy, and the sample is water-like after being placed for 5 days.
[0077] Depend on Figure 5 It can be seen that the microspheres prepared in Comparative Example 2 have no strength and become mud after the sample preparation and spreading process. The sample becomes hardened after being left for 7 days.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength glass precursor microsphere that is not easy to absorb moisture, characterized in that: The method comprises the following raw materials: silica sol, salt and boric acid, wherein the salt is acetate and nitrate; wherein the molar ratio of acetate in the acetate to nitrate in the nitrate is 3-5:1, the mass ratio of boric acid to silica sol is 6-8:100, and the mass ratio of salt to boric acid is 44-58:6-8; The mass fraction of SiO2 in the silica sol is 10-30%, and the particle diameter of SiO2 is 1-20nm; The method for preparing the high-strength glass precursor microspheres that are not easy to absorb moisture comprises the following steps: (1) adding water to the raw materials acetate, nitrate and boric acid to prepare raw material aqueous solutions, and then mixing them evenly to obtain a mixed solution; (2) heating the mixed solution obtained in step (1) under stirring conditions, diluting the silica sol with water, and then adding the diluted silica sol by atomization to obtain a white emulsion; (3) spray drying the white emulsion obtained in step (2) to obtain high-strength glass precursor microspheres that are not easy to absorb moisture; In step (2), the pH value of the white emulsion is 5.5-7.
2. The high-strength glass precursor microspheres that are not easy to absorb moisture according to claim 1, characterized in that: The acetate is a mixture of two or three of calcium acetate, lithium acetate, aluminum acetate, sodium acetate and potassium acetate.
3. The high-strength glass precursor microspheres that are not easy to absorb moisture according to claim 1, characterized in that: The nitrate is a mixture of three, four or five of calcium nitrate, lithium nitrate, aluminum nitrate, sodium nitrate, potassium nitrate and magnesium nitrate.
4. The high-strength glass precursor microspheres that are not easy to absorb moisture according to claim 2 or 3, characterized in that: The Ca in the salt 2 + , Li + 、Al 3+ 、Na + , K + Mg 2+ The molar ratio is 15-18:18-20:1:4-8:1-5:1-5.
5. The high-strength glass precursor microspheres that are not easy to absorb moisture according to claim 1, characterized in that: In step (1), the mass concentration of the raw aqueous solution is 8-12%.
6. The high-strength glass precursor microspheres that are not easy to absorb moisture according to claim 1, characterized in that: In step (2), heating is performed to 40-70°C.
7. The high-strength glass precursor microspheres that are not easy to absorb moisture according to claim 1, characterized in that: In step (3), spray drying is performed at 120-200°C.
8. Use of the high-strength glass precursor microspheres that are not easy to absorb moisture according to any one of claims 1 to 7 in the preparation of hollow glass microspheres.
Citation Information
Patent Citations
Titanium-doped gel and preparation method thereof
CN105837033A